Numerical analysis of the properties of nanofluids and their impact on the thermohydrodynamic phenomenon in a heat exchanger. (2021) - Salhi, Jamal-Eddine; Zarrouk, Tarik; Salhi, Najim
Abstract: In the present study, a numerical study was carried out to study the impact of the cooling fluid's thermophysical properties on the improvement of heat transfer in a cooling system. The chosen field of study is a channel of constant circular sections crossed by forced convective and turbulent flow. The wall being raised to a uniform and constant temperature Tw. The cooling fluids used are nanofluids based on pure water, adding nanoparticles of Al2 O3 or nanoparticles of ZnO. The Reynolds number of the analysis belongs to the range (50000, 100000), and the concentration of the nanoparticles is between 1% and 3%. The diameters of the nanoparticles chose in the range of 30 nm to 60 nm. The discretization of the system equations governing the problem is performed using a finite volume scheme, and its resolution is performed numerically by a stable scheme with the SIMPLE algorithm to solve the velocity–pressure coupling problem. The standard k-ε model models turbulence. The numerical results calculated include, in particular, the Nusselt number (Nu), the coefficient of friction (Cf ), the pressure difference (dP), the heat flow (Q), and the thermal efficiency. The results show that the system's thermal efficiency increases with an increasing volume concentration of the nanoparticles. Nanofluids are then better heat transfer fluids for a cooling system.